The use of subgingival chlorhexidine chip in the treatment of periodontal disease - Luković Natalija; Zelić Obrad; Čakić Saša (Stomatološki glasnik Srbije, 2006)
Due to the infective nature of periodontal disease several local devices have been used to overcome the limited efficacy of conventional periodontal treatment. However, local concentration of these medicaments, especially over time, raises the question of expediency of their use. Local delivery systems allow the therapeutic agents to be targeted to the diseased site for a long time. These systems, when retained in the periodontal pocket, can release the antimicrobial agents at levels that are 10- to 100-fold higher than the levels that can be delivered by systemic antibiotics. Several different drug delivery systems have been used in controlled clinical trials: fibers, gels and chips. The most frequently used antimicrobials are antibiotics (tetracycline, minocycline), hemotherapeutics (metronidazole), and antiseptics (chlorhexidine dicluconate). In the present paper the method of chlorhexidine chip application is analyzed. We discussed the results of studies that evaluated the efficacy of a controlled-release of biodegradable chlorhexidine chip when used as an adjust to scaling and root planning (SRP) in adult periodontitis.